Tanggung Jawab Orang Tua Terhadap Pendidikan Agama Dan Kemampuan Membaca Al-Qur’an Anak - RIZKAN SYAHBUDIN (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2015)
The three institutions as a basic determinant of child development education, ie informal, formal and informal, but clearly the basis basik child is informal institutions, because these institutions where the role of parents is very big influence on a child's development in the future. Prophet Muhammad laid the foundation of a child's educational development in the hadith: